FAKTOR-FAKTOR RESIKO KEJADIAN HIPERTENSI DALAM KEHAMILAN DI RUMAH SAKIT IBU DAN ANAK MUSLIMAT JOMBANG: Risk Factors Of Hypertension In Pregnancy In Jombang Muslimat And Child Hospitals - Nur Jannah, Rintisiati; Hayu Lestari, Rini; Kolifah, Kolifah (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
Hypertension in Pregnancy (HDK) is 6-10% of pregnancy complications and is one of the three highest causes of maternal mortality and morbidity, (Alatas, 2019). For pregnant women in Indonesia, HDK is included in the three highest ranking causes of death for pregnant women, and there are more than 30% of pregnant women who die from HDK. The purpose of this study was to analyze the risk factors for hypertension in pregnancy at RSIA Muslimat Jombang.This research method is Analytical, with a Cross Sectional design with secondary data from patient medical records at RSIA Muslimat Jombang from 14 April 2023 to 20 April 2023. Data were analyzed by Chi Square test.The results showed that 166 patients experienced hypertension in pregnancy. The results of the chi square test showed a significant relationship between age (p = 0.000), number of pregnancies (p = 0.000), nutritional status (p = 0.048) and history of hypertension (p = 0.027) to the incidence of HDK.To achieve a physiological gestational age, optimal conditions are needed, namely good nutritional status during pregnancy, parity must be considered so that it does not become a pathological pregnancy and medical history must be considered so as not to cause complications in the current pregnancy.